On the Use of Photographic Images as Evidence in Sexual Violence Cases - Bonorino, Pablo R. (EUNOMÍA. Revista en Cultura de la Legalidad, 2023)
Is it necessary to include detailed descriptions of the content of photographic images used as evidence in sexual violence cases in court rulings? In this article, we will argue (1) that photographic images are introduced into an evidentiary argument through statements describing their content and statements interpreting their content, (2) that both types of statements are the product of mental inferences (hypercoded and hypocoded) which can be made explicit verbally about subjecting them to intersubjective control, (3) that in cases of sexual violence, decision-makers should argue in an enthymematic way when justifying their decisions, incorporating only the most general premises of their hypocoded inferences and avoiding reproducing their hypercoded inferences. In this way, they could guarantee the accused's right to defence and effective judicial protection without unnecessarily infringing on the victims' right to privacy.
Keywords: evidentiary argumentation; photographic images; visual perception; semiotic inferences; grounds for court rulings; crimes against sexual freedom